Influence of indoor air temperature variation on office work performance - Valančius, Rokas; Jurelionis, Andrius (Journal of Environmental Engineering and Landscape Management, 2013)
Indoor air quality as well as thermal comfort has a significant effect on productivity of the employees in office buildings. It may reduce work performance and cause financial losses in a long term perspective. Sudden temperature swings may have an impact on the work performance as well. The aim of this study was to assess the change of office work performance of the same individuals affected by unsteady air temperature.Office work was simulated in the test chamber with two workplaces and two persons at the time. 78 individuals of age 19 to 31 were divided into three groups and took participation in performing productivity tests. Two cases were analysed: one with the temperature rise from +22 to +26 °C and another with the temperature drop from +22 to +18 °C. The same tests were performed with the placebo group under a constant air temperature of +22 °C.Results of the study showed that subjects in the placebo group performed better while executing tasks for the second time and the overall productivity was higher by 2.1%. In case of the air temperature raise, performance reduced by 0.1% and the overall productivity improved by 5.2% in case of air temperature drop.First published online: 08 Feb 2013